Cerebellar and Visual Gray Matter Brain Volume Increases in Congenital Nystagmus - Hüfner, Katharina; Stephan, Thomas; Flanagin, Virginia L.; Deutschländer, Angela; Dera, Thomas; Karch, Cornelia; Linn, Jennifer; Glasauer, Stefan; Dieterich, Marianne; Strupp, Michael; Brandt, Thomas (Frontiers in Neurology, 2011)
Structural brain abnormalities associated with congenital nystagmus are still unknown. In some patients with congenital nystagmus additional sensory, metabolic or gross structural alterations can be detected. In the present study voxel-based morphometry was used to compare the gray matter brain volumes of 14 individuals with congenital nystagmus without associated sensory, metabolic or obvious structural alterations (i.e. idiopathic congenital nystagmus) to those of a group of controls. Further, gray matter brain volumes were correlated with nystagmus severity as measured by sway path. Intergroup comparison exhibited significant volume increases in the human motion sensitive complex V5/MT+, the fusiform gyrus and the middle occipital gyrus bilaterally in congenital nystagmus. These volume increases may be associated with excess visual motion stimulation due to involuntary retinal slip of the visual scene. A positive correlation (linear model) of nystagmus sway path with cerebellar gray matter volume was seen in the following areas: vermal parts VIII-X as well as hemisphere lobule II, hemisphere VI, crus I, crus II, and lobule VII-IX bilaterally. There is evidence that the reported gray matter volume changes in the vestibulo-cerebellum, which correlated with nystagmus sway path, might be related to the subjects` attempt to maintain fixation, rather than be due to the generation of nystagmus.